Maternal Risk Factors for Autism Spectrum Disorder - Noor Abdulmohsin Mohammed; Najdat Sh. Mahmood; Jalil I. Alezzi; Bassim Mohammed Ahmed; Mohamed Aydaroos Aljefri (Diyala Journal of Medicine, 2024)
Background: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder characterized by deficits in social communication, restricted interests, and repetitive behaviors. The etiology of ASD is multifactorial, involving genetic, environmental, and maternal factors. Recent studies have suggested maternal factors, such as advanced maternal age, high BMI, smoking, and depression during pregnancy, as significant risk factors for ASD. Objective: This study aims to investigate the maternal risk factors that contribute to ASD in children at Diyala, Iraq. Patients and Methods: This case-control study was conducted on 150 children, comprising 75 children diagnosed with ASD and 75 healthy children as a control group. The study was carried out from August 2023 to May 2024 in Diyala, Iraq. Data collection included comprehensive demographic, social, obstetric, and maternal health histories. ASD diagnosis was confirmed using the Childhood Autism Rating Scale 2 (CARS-2). A logistic regression analysis was performed to assess the association between maternal risk factors and ASD. Results: The study revealed several significant maternal risk factors for ASD. Advanced maternal age at pregnancy (mean age 28.1 years in cases vs. 22.9 years in controls, p=0.001), high maternal BMI (mean BMI 26.9 in cases vs. 24.4 in controls, p=0.0001), maternal smoking (6.7% in cases vs. 0% in controls, p=0.023), and maternal depression during pregnancy (22.7% in cases vs. 0% in controls, p=0.0001) were all significantly associated with an increased risk of ASD. The use of stimulating hormones before pregnancy also showed a significant association (21.3% in cases vs. 4% in controls, p=0.001). Parity, particularly having 1-2 pregnancies, was also a significant risk factor (p=0.002). Conclusion: This study identifies advanced maternal age, high BMI, smoking, depression, and the use of stimulating hormones before pregnancy as significant maternal risk factors for ASD in children. Keywords: Autism, ASD, maternal age and autism, maternal illness and autism.